Novel Oral Poliovirus Vaccine 2 Safety Evaluation during Nationwide Supplemental Immunization Activity, Uganda, 2022 - Tobolowsky, Farrell A; Nsubuga, Fred; Gilani, Zunera; Kisakye, Annet; Ndagije, Helen; Kyabayinze, Daniel; Gidudu, Jane F (Centers for Disease Control and Prevention, 2024)
Abstract Given its enhanced genetic stability, novel oral poliovirus vaccine type 2 was deployed for type 2 poliovirus outbreak responses under World Health Organization Emergency Use Listing. We evaluated the safety profile of this vaccine. No safety signals were identified using a multipronged approach of passive and active surveillance.
Keywords: vaccine-related paralysis; novel oral poliovirus vaccine type 2; Safety Evaluation; Immunization; Uganda